Mencetak Guru Berkarakter melalui Supervisi Pendidikan Berbasis Profetik - Toha Ma'sum (Sekolah Tinggi Ilmu Tarbiyah Al-Urwatul Wutsqo Jombang, 2019)
Education is an investment where the process requires concrete steps to make it happen; it can be taken through informal, non-formal and formal education, which in the process the teacher's role is significant and urgent, in addition to education and teaching, it is also demanded as professionals. One effort to improve teacher professionalism through the supervision process. The purpose of this study is to find out and describe the efforts made by a head in enhancing the competence and abilities of the teacher through the process of supervision activities carried out by internalizing prophetic values. The type of this research is literature, with a pattern of qualitative research, the purpose of this research is understanding, data is naturalistic, the method is inductive, reporting is descriptive and analytical. Data analysis techniques are inductive, deductive and comparative methods. The results of this study are that in carrying out supervision activities, both supervisors and supervised teachers can internalize prophetic values ​​in their actions. That way these activities can be valuable for supervisors and supervised ones. The conclusion of this study is that as a supervised (object of supervision), one must accept it as a form of worship as a relationship between fellow believers to remind each other in terms of goodness, display and appear as they are, honest and not manipulate (eg documents), carry out responsibilities, improvements and judgments for oneself before they are considered to be ended later. And no less important is, intending to improve and improve quality.